2017
DOI: 10.3390/su9101800
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Levels of CSR Disclosure by Forestry Companies in China

Abstract: Abstract:With the international community's increasing concern for social and environmental problems, the fulfilment and disclosure of corporate social responsibility (CSR) has been advocated and promoted across the world. Forestry companies, which are particularly sensitive to environmental and social issues, are increasingly developing and improving their levels of CSR disclosure. However, information on emerging country contexts is still lacking. To fill this gap, this study focuses on Chinese forestry comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Studies using data from developing countries have also drawn similar conclusions. Lu et al (2017) [31] selected Chinese forestry listed firms as their sample. The results indicated that the sizes and the degrees of ownership concentration of firms had significant positive effects on the disclosure of CSR.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Studies using data from developing countries have also drawn similar conclusions. Lu et al (2017) [31] selected Chinese forestry listed firms as their sample. The results indicated that the sizes and the degrees of ownership concentration of firms had significant positive effects on the disclosure of CSR.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Moreover, we included several control variables related to company characteristics, such as size [88,97], profitability [35,77,98], regulation [31], internationalization [32,33], and industry sensitivity [99] based on the previous literature.…”
Section: Control Variablesmentioning
confidence: 99%
“…Literature suggests that more visible firms, in terms of size or media exposure, attract attention from a broader community and that they react to visibility pressure through a greater commitment to social and environmental disclosure [43,[63][64][65][66][67]. An increase in a firm's size also fosters the capability to absorb signal costs in terms of CSR disclosure extent.…”
Section: Hypothesismentioning
confidence: 99%